Goosegrass Biology and Control in Fruiting Vegetables, Cucurbits, and Small Fruits - Andrew W. MacRae (EDIS, 2010)
HS1178, a 2-page illustrated fact sheet by Andrew W. MacRae, describes this large grass common in mulched row crops and blueberry production fields — classification, seedling identification, mature plant, management considerations, and chemical control. Includes references. Published by the UF Department of Horticultural Sciences, May 2010.